2011
DOI: 10.1051/0004-6361/201117797
|View full text |Cite
|
Sign up to set email alerts
|

Herscheldiscovery of a new class of cold, faint debris discs

Abstract: We present Herschel PACS 100 and 160 μm observations of the solar-type stars α Men, HD 88230 and HD 210277, which form part of the FGK stars sample of the Herschel open time key programme (OTKP) DUNES (DUst around NEarby S tars). Our observations show small infrared excesses at 160 μm for all three stars. HD 210277 also shows a small excess at 100 μm, while the 100 μm fluxes of α Men and HD 88230 agree with the stellar photospheric predictions. We attribute these infrared excesses to a new class of cold, faint… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 22 publications
(20 reference statements)
1
54
1
Order By: Relevance
“…, and producing extended emission at wavelengths up to 250 µm, which is not observed. These properties would place it amongst those "cold disc candidates" identified in Eiroa et al (2011), Eiroa et al (2013), and Marshall et al (2013), albeit much brighter than those previously identified and therefore inconsistent with the explanation for the phenomenon proposed in Krivov et al (2013). We therefore disfavour this explanation for the shape of the SED.…”
Section: Hip 22263contrasting
confidence: 55%
“…, and producing extended emission at wavelengths up to 250 µm, which is not observed. These properties would place it amongst those "cold disc candidates" identified in Eiroa et al (2011), Eiroa et al (2013), and Marshall et al (2013), albeit much brighter than those previously identified and therefore inconsistent with the explanation for the phenomenon proposed in Krivov et al (2013). We therefore disfavour this explanation for the shape of the SED.…”
Section: Hip 22263contrasting
confidence: 55%
“…The colder disc component postulated here would be analogous to the "cold debris discs" candidates identified in Eiroa et al (2011). In addition to the requirement that the grains are large, they should have a low absorption in the visible, perhaps through the presence of icy material on the grain surface.…”
Section: Circumstellar Emissionmentioning
confidence: 70%
“…Several intriguing debris disc candidate sources have been identified in DUNES Herschel PACS and SPIRE observations of nearby stars (Eiroa et al 2011). These "cold disc candidates" exhibit only marginal excess emission at wavelengths shortward of 100 µm, a peak in the spectral energy distribution (SED) at 160 µm and no detectable sub-mm excess in SPIRE observations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, from a purely observational point of view, a huge population of fairly massive, but cold disks A&A 537, A110 (2012) could still be hidden below current sensitivity limits. Some of these will be revealed by Herschel (Pilbratt et al 2010;Eiroa et al 2011).…”
Section: Introductionmentioning
confidence: 96%